The design of business : why design thinking is the next competitive advantage - Martin, Roger L. (Lahore : Harvard Business Review Press, 2009)
Most companies today have innovation envy. They yearn to come up with a game$1 (Bchanging innovation like Apple's iPod, or create an entirely new category like Facebook. Many make genuine efforts to be innovative$1 (Bthey spend on R&D, bring in creative designers, hire innovation consultants. But they get disappointing results. Why? In The Design of Business , Roger Martin offers a compelling and provocative answer: we rely far too exclusively on analytical thinking, which merely refines current knowledge, producing small improvements to the status quo. To innovate and win, companies need design thinking. This form of thinking is rooted in how knowledge advances from one stage to another$1 (Bfrom mystery (something we can't explain) to heuristic (a rule of thumb that guides us toward solution) to algorithm (a predictable formula for producing an answer) to code (when the formula becomes so predictable it can be fully automated). As knowledge advances across the stages, productivity grows and costs drop-creating massive value for companies. Martin shows how leading companies such as Procter & Gamble, Cirque du Soleil, RIM, and others use design thinking to push knowledge through the stages in ways that produce breakthrough innovations and competitive advantage. Filled with deep insights and fresh perspectives, The Design of Business reveals the true foundation of successful, profitable innovation.s
Keywords: Creative ability in business; Creative thinking; Knowledge management; Lateral thinking; Management